Overview of Microbiological Quality in Refillable Drinking Water Depots (DAMIU) in Barrang Lompo Island, Makassar City in 2024 - Fajrin, Marwah; Birawida, Agus Bintara; Sila, Nurlia (Environmental and Public Health Maritime Journal, 2025)
BACKGROUND: The high demand for drinking water has driven the popularity of Refilled Drinking Water Station consumption. However, in terms of quality, water from refill stations is not always guaranteed to be clean, as it is at risk of bacterial contamination. AIM: This study aims to identify the presence of pathogenic bacteria in Refilled Drinking Water Station operating on Kodingareng Lompo Island, Barrang Caddi Island, and Lae-Lae Island, Makassar City. METHODS: This research is a quantitative observational study with a descriptive approach. The population of this study was all refill drinking water depots that are actively operating on Barrang Lompo Island, the research sample was based on inclusion criteria. RESULTS: The findings indicate that four out of six Refilled Drinking Water Station across these three islands are contaminated with pathogenic bacteria, specifically total coliform and Escherichia coli (E. coli). Four out of the six Refilled Drinking Water Station were contaminated with total coliform bacteria, with varying bacterial counts ranging from 2 to 243. The Refilled Drinking Water Station with the highest total coliform count was Depot E1, with 243 bacteria, while the Refilled Drinking Water Station with the lowest total coliform count (zero bacteria) were Depot B1 and Depot G1. One out of six Refilled Drinking Water Station was contaminated with E. coli, specifically Depot E1, which had an E. coli count of 11. The four contaminated Refilled Drinking Water Station failed to meet the standards set by Permenkes No. 43 of 2014 regarding building location, depot equipment, and hygiene and sanitation of depot handlers, with feasibility scores below 70%. CONCLUSION: All Refilled Drinking Water Station use bore wells and reverse osmosis for water treatment. However, some Refilled Drinking Water Station remain contaminated with total coliform and E. coli, with factors such as location, equipment, and hygiene and sanitation of Refilled Drinking Water Station handlers contributing to this contamination.